El Comentario de Santo Tomás a la Política de Aristóteles: un análisis desde el Prooemium - Barrera, Jorge Martínez (Veritas (Porto Alegre), 2006)
Os prólogos dos comentários de Tomás de Aquino às obras de Aristóteles são de suma importância, porque neles o autor apresenta o que se poderia denominar “o marco conceptual” do trabalho que está empreendendo. No caso do Comentário à Política, o conceito fundamental é o conceito de natureza. A afirmação de que existe uma “imitação da natureza” significa, para Tomás, muito mais do que representou para seus antecessores. PALAVRAS-CHAVE – Tomás de Aquino. Comentário. Política. Natureza. Imitação. ABSTRACT The prologs of Thomas Aquinas to the works of Aristotle are of main importance, because in these prologs the author presents what could be called “the conceptual mark” of the tasks he is undertaking. In the case of the Comments to the Politics, the fundamental concept is the concept of nature. The statement that there is an “imitation of nature” means, for Thomas, much more that it had represented for his antecessors. KEY WORDS – Thomas Aquinas. Comment. Politics. Nature. Imitatio.